Динамические характеристики рекуперативного противоточного теплообменного аппарата - Шевелев, Александр Александрович; Тарасенко, Александр Николаевич (НТУ "ХПИ", 2012)
Численным методом бегущего счета решена связанная система дифференциальных уравнений динамики рекуперативного противоточного теплообменника. Рассчитаны отклики входных температур потоков на экспоненциальный закон увеличения входной температуры греющего теплоносителя.

The numeral method of running account is decide coupled system of differential equations dynamics of recuperative counterflow heat exchanger. Сalculated response of input flow temperatures for the exponential law of increasing the inlet temperature of heating fluid. shows the effect of the ratio of water equivalents heat carrying agents during the transition for a wide range variation the rate of increase inlet temperature of the heating medium.
Keywords: силовые режимы; удельные усилия; качество профилей; трение; конечное формообразование; specific stress; mode of deformation; friction; profile quality; final shaping